USP5‐dependent HDAC1 promotes cisplatin resistance and the malignant progression of non–small cell lung cancer by regulating RILP acetylation levels - Rongguo Lu; Yulin Jin; Mingfeng Zheng (Thoracic Cancer)
Abstract Background Non‐small cell lung cancer (NSCLC) is a leading cause of cancer‐related deaths worldwide, with cisplatin (DDP) resistance being a significant challenge in its treatment. Histone deacetylase 1 (HDAC1) has been implicated in the regulation of NSCLC progression; however, its role in the resistance of NSCLC to DDP remains unclear. Methods The mRNA levels of HDAC1, ubiquitin specific peptidase 5 (USP5), and Rab interacting lysosomal protein (RILP) were analyzed by quantitative real‐time polymerase chain reaction. The protein expression of HDAC1, multidrug resistance protein 1 (MRP1) and RILP was detected by western blotting assay or immunohistochemistry assay. The IC50 value of DDP was determined using a cell counting kit‐8 assay, while cell proliferation, apoptosis, and invasion were assessed using 5‐Ethynyl‐2’‐deoxyuridine assay, flow cytometry, and trans well invasion assay, respectively. Cancer stem‐like cell properties were analyzed by a sphere formation assay. The interaction between USP5 andHDAC1 was investigated using MG132 assay and co‐immunoprecipitation (Co‐IP).RILP acetylation was analyzed by a Co‐IP assay. A xenograft mouse model assay was employed to study the in vivo effects of HDAC1 silencing on DDP sensitivity. Results HDAC1 expression was upregulated in DDP‐resistant NSCLC tissues and cells. Silencing HDAC1 enhanced the sensitivity of NSCLC cells to DDP, inhibited cell proliferation, invasion, and the formation of microspheres and induced cell apoptosis. USP5 was found to deubiquitinate and stabilize HDAC1 in DDP‐resistant NSCLC cells. Moreover, HDAC1 overexpression reversed the effects induced by USP5 silencing. HDAC1 also sensitized Rab‐interacting lysosomal protein (RILP) acetylation in DDP‐resistant NSCLC cells, and RILP upregulation counteracted the effects of HDAC1 overexpression in DDP‐resistant NSCLC cells. HDAC1 silencing also improved the sensitivity of tumors to DDP in vivo. Conclusion USP5‐dependentstabilization of HDAC1 contributed to cisplatin resistance and the malignancy of NSCLC by diminishing the levels of RILP acetylation, which suggested that targeting the HDAC1‐USP5axis might represent a novel therapeutic strategy for overcoming DDP resistance in NSCLC patients.